Synthesis and Characterization of Nanoparticles from Natural Materials - Shahad Saadi Ismail Jumaa; Randa Qassem Ismail Ibrahim; Najm Sufyan Najm Abdullah; Raghad Khaled Abdul Saleh; Mohammed Youssef Armit Kazem (Genius Journals, 2024)
In this paper , honey was used as a raw material to prepare carbon nanoparticles, as it is a natural substance rich in carbon, and many techniques were used, such as the X-ray diffraction device (XRD), the energy-dispersive X-ray spectroscopy device (EDS), and the microscope. Scanning electron microscope (SEM), to detect the resulting nanomaterial. The results showed the presence of nanoparticles with a range between 40-50 nanometers. The biological effectiveness of the resulting material in inhibiting bacteria was measured using the sensitivity test method (disk diffusion method by taking different concentrations of the substance and applied it to two types of bacteria, positive and negative, namely: Staphylococcus aureus and E.coli, where the results showed that the prepared minutes have an inhibitory effect on both types of bacteria.Therefore, we conclude from this study that the preparation of carbon nanoparticles gave good preliminary results that are encouraging for future work as antibacterial agents.
Keywords: carbon; nanoparticles; Natural Materials; X-ray